1958
DOI: 10.1246/bcsj.31.734
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States of p-Benzoquinone. IV. Infrared Spectrum and Assignment of Vibrational Frequencies in the Ground Electronic State

Abstract: The infrared absorption spectra of p-benzoquinone in carbon disulfide and carbon tetrachloride solutions in rock salt region are measured and interpreted together with the Raman data reported by Stammreich and Forneris. A complete, although more or less tentative, assignment of the fundamental frequencies to modes of vibrations is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Figure 2b shows the results of indexing the data from this study with the refined unit cell. Limited information on the normal modes of vibration of THQ was found in the literature, but the vibrational spectra of THQ collected during this study under atmospheric conditions have some similarities to that previously observed for the parent molecule of 1,4benzoquinone [13,[18][19][20][21]. With twenty-two atoms per molecular unit of THQ, sixty unique normal modes of vibration are dictated for THQ at ambient pressure.…”
Section: A Properties At Ambient Pressuresupporting
confidence: 55%
“…Figure 2b shows the results of indexing the data from this study with the refined unit cell. Limited information on the normal modes of vibration of THQ was found in the literature, but the vibrational spectra of THQ collected during this study under atmospheric conditions have some similarities to that previously observed for the parent molecule of 1,4benzoquinone [13,[18][19][20][21]. With twenty-two atoms per molecular unit of THQ, sixty unique normal modes of vibration are dictated for THQ at ambient pressure.…”
Section: A Properties At Ambient Pressuresupporting
confidence: 55%
“…26,30,31 The assignment of this spectrum, in particular that of the pair of intense bands at 1650-1670 cm…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…1 shows the absorption spectra of UQ 10 and MQ (vitamin K 1 ). The most prominent signal of UQ seen between 1660 and 1640 cm − 1 includes the coordinates of the ν(C_O) vibration [13,[17][18][19][20][21]. The broadness of the signal of the isolated Q in solution points towards the presence of several interaction partners of C_O group with water.…”
Section: Infrared Spectra On Oxidized Quinonesmentioning
confidence: 99%
“…The first published attempt at a complete vibrational assignment of quinones was made by Anno and Sado [17] who obtained infrared spectra of quinone solutions. Since then a significant number of studies on the vibrational properties of quinones were made describing the signal characteristic for the different redox states, the influence of isotope labeling, and comparing the different types of quinones.…”
Section: Infrared Spectra On Oxidized Quinonesmentioning
confidence: 99%